1991
DOI: 10.1177/030006059101900308
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Fibre on Upper and Lower Gastro-Intestinal Transit Times and Faecal Bulking

Abstract: A total of 10 obese patients (body mass index greater than 25) undergoing treatment with a very low-calorie (330 kcal/day) liquid diet were treated without and with 10.5 or 21 g/day dietary fibre. Mean (+/- SE) faecal bulking increased significantly (P less than 0.001) in a dose-dependent manner from 314.8 +/- 54.4 g on a fibre-free diet to 517.2 +/- 45.4 g and 748.9 +/- 78.5 g, respectively, over 5 days on diets containing 10.5 and 21 g/day dietary fibre. Total mean colonic transit time decreased from 53.9 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
1
1
Order By: Relevance
“…However, it has been reported that fecal bulking increases significantly in a dose-dependent manner with dietary fiber supplementation (Staniforth et al, 1991). In our experiment, the cecal content in the RBI diet group (consuming 10% dietary fiber) was significantly greater than that in the CI diet group (consuming 5% dietary fiber).…”
Section: Discussioncontrasting
confidence: 55%
“…However, it has been reported that fecal bulking increases significantly in a dose-dependent manner with dietary fiber supplementation (Staniforth et al, 1991). In our experiment, the cecal content in the RBI diet group (consuming 10% dietary fiber) was significantly greater than that in the CI diet group (consuming 5% dietary fiber).…”
Section: Discussioncontrasting
confidence: 55%
“…More folds in the colon would result in increases in the propulsive force, increasing rate of bolus passage along the colon. The increasing fiber content in leaf meal based diets is likely to have stimulated colon motility (Staniforth, Baird, Fowler, & Lister, 1991;Brownlee, Dettmar, Strugala, & Pearson, 2006;Zeng, Lazarova, & Bordonaro, 2014) resulting in increases in the number of colon folds. Such segmental contractions result in increased water absorption and electrolyte exchange (Maykel & Opelka, 2004) and possibly reduced contact time between digesta and intestinal lumen.…”
Section: Discussmentioning
confidence: 99%
“…Addition of wheat bran to the diet has been shown to reduce BTT but this effect may be due to the physical form of the wheat bran used rather than a particular constituent [28,41,45,46]. Other studies have reported no change in BTT after ingestion of wheat bran or pectin [47], oat hull fibre [48] or green lentils [49]. Dietary fibre consumption is one of many variables that influence colonic function.…”
Section: Effects Of a Chickpea-supplemented Dietmentioning
confidence: 99%